Effect of introducing antenatal diagnosis on reproductive behaviour of families at risk for thalassaemia major. Issue 6228 (7th June 1980) - Modell, B; Ward, R H; Fairweather, D V
Abstract : Families who were at risk of producing a child with thalassaemia major were studied to determine the sequential effects on their reproductive behaviour of knowing the risk and, subsequently, of knowing that antenatal diagnosis was available. Knowing the risk caused them virtually to stop reproduction and to seek termination of 70% of pregnancies, most of which were accidental. The introduction of antenatal diagnosis in 1975 permitted the resumption of nearly normal reproduction by at-risk families, with fewer than 30% of pregnancies being terminated for thalassaemia major. All couples at risk for thalassaemia major should be detected and counselled before they produce an affected child; responsibility for either choosing or refusing antenatal diagnosis should be theirs alone.